Charging back up the hill : workplace recovery after mergers, acquisitions, and downsizings - Marks, Mitchell Lee (Jossey-Bass business & management series, 2003)
"This guide, by the internationally renowned management consultant Mitchell Lee Marks, presents an innovative process for workplace recovery. Charging Back Up the Hill lays out the essential elements of successful transition management, providing the techniques and tips that executives and managers can use to lead the organization following a merger, acquisition, downsizing, or other major transition. Marks offers invaluable advice to any organization ready to change and charge ahead in the twenty-first century."--BOOK JACKET.